2021
DOI: 10.1007/s00122-021-03804-3
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of THOUSAND-GRAIN WEIGHT 6 grain weight genes in wheat and rice indicates a role in pollen development rather than regulation of auxin content in grains

Abstract: The THOUSAND-GRAIN WEIGHT 6 genes (TaTGW6 and OsTGW6) are reported to result in larger grains of wheat and rice by reducing production of indole-3-acetic acid (IAA) in developing grains. However, a critical comparison of data on TaTGW6 and OsTGW6 with other reports on IAA synthesis in cereal grains requires that this hypothesis be reinvestigated.Here, we show that TaTGW6 and OsTGW6 are members of a large gene family that has undergone major, lineage-specific gene expansion. Wheat has nine genes, and rice three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The TaTGW6‐A1 gene was reported by Hanif et al 14 to be an ortholog of the rice THOUSAND‐GRAIN WEIGHT 6 ( TGW6 ) gene 53 . The gene functions to increase grain weight in bread wheat by reducing production of indole‐3‐acetic acid (IAA) in developing grains, although this has now been disputed by Kabir and Nonhebel, 54 who instead, suggested a role in pollen development. The QTL for TGW on chromosome 4AL was also only detected when grain weight was measured using digital image analysis (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The TaTGW6‐A1 gene was reported by Hanif et al 14 to be an ortholog of the rice THOUSAND‐GRAIN WEIGHT 6 ( TGW6 ) gene 53 . The gene functions to increase grain weight in bread wheat by reducing production of indole‐3‐acetic acid (IAA) in developing grains, although this has now been disputed by Kabir and Nonhebel, 54 who instead, suggested a role in pollen development. The QTL for TGW on chromosome 4AL was also only detected when grain weight was measured using digital image analysis (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study elaborated that TGW6 encodes an Investment Adviser Association (IAA)‐glucose hydrolase, which can hydrolyze IAA‐glucose into IAA and glucose by liquid chromatography‐electrospray ionization‐tandem mass spectrometry (Ishimaru et al ., 2013). Surprisingly, a recent research suggested that OsTGW6 and TaTGW6 might not regulate grain size via the hydrolysis of IAA‐glucose, because OsTGW6 and its clade I homologues are expressed in early inflorescences but not in developing kernels by microarray data analysis and RNA‐seq analyses, as well as wheat grains had undetectable levels of ester IAA in comparison with free IAA (Kabir & Nonhebel, 2021). However, we found that increased levels of TGW6 were detected in panicles of DAF1, DAF3, and DAF5 by Western blotting analyses (Figs 6a, S16), suggesting that TGW6 functions in developing seeds.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this problem, another study has focused on determining the genes controlling rice grain weight. For example, TGW6 has been shown to boost rice production by 15% when its function is blocked (Kabir and Nonhebel, 2021). CRISPR/Cas9 sitedirected mutagenesis has been used to improve maintainer lines and get desirable traits faster in rice hybrid breeding methods based on this knowledge (Romero and Gatica-Arias, 2019).…”
Section: Novel Approaches In Breeding Cropsmentioning
confidence: 99%